Antibacterial Activity of Extra Ethanol Kopasanda Leaves (Chromolaena Odorate L.) Against Pathogenic Bacteria of Urinary Tract Infection by TLC-Bioautography and Agar Diffusion - Wirawan, Alif Yusra; Kosman, Rachmat; Herwin, Herwin (Journal Microbiology Science, 2023)
Kopasanda  (Chromolaena odorata L.) leaves are one of the plants (herbs) containing various types of secondary metabolites, including saponins, tannins, alkaloids, and flavonoids, which function as antibacterial agents used as wound medicine for the community. This study aims to determine the antibacterial activity of the ethanol extract of Kopasanda (Chromolaena odorate L.) leaves using the TLC-bioautography and diffusion methods. The results of the antibacterial activity screening test obtained the active extract at a concentration of 0.1% against Escherichia coli and Staphylococcus aureus. The results of the antibacterial activity test using the TLC-Bioautography method with the eluent N-Hexane:Ethyl Acetate (4:1) showed results from Staphylococcus aureus bacteria with Rf values = 0.90, 0.78, 0.67, 0.52, 0.38, 0.27, 0.14, 0.05, and Escherichia coli bacteria with Rf values = 0.90, 0.52, 0.38, 0.27, 0.14, 0.05. Based on the results of testing the antibacterial activity with the agar diffusion method, the largest diameter of the inhibition zone at a concentration of 10% was obtained for Escherichia coli bacteria with an inhibition zone diameter of 13.59 mm, and Staphylococcus aureus with an inhibition zone diameter of 15.52 mm.